The Effectiveness of the Assignment of Dialogue with Shiah and Apostacy Groups via Facebook in the Coursework of Dakwah Information Technology - Muhamad Faisal Ashaari; Azimah Misrom; Badlihisham Mohd Nasir (International Islamic Schools Alliance, 2016)
Nowadays, there are parties who deliberately spread doubts about Islam through the new media. Moreover, they attack Islam emotionally. Given that, students who pursue the course “Da'wah through Information Technology” in UKM are disclosed with those doubts and they are assigned to have dialogues with Shiite groups and apostate through Facebook. Indeed, the dialogue is a method of teaching and learning that can pass at least the third stage of Bloom Taxonomy and at the same time it can hone their skill of arguing. Students were asked to have dialogues with both groups to examine, to evaluate, to discuss, and to answer any doubt that they rise. This article discusses the findings of research on 50 students who pursue this course in Semester 1, 2013/14. The study found that this task really challenge the ability in arguing and students’ knowledge. Although they have tried the best, many feel that they could not convince their dialogue partners. Throughout the course, they have been using various means to develop the existing knowledge mainly referring the problem to friends and teachers in order to defend the argument in the dialogue. Therefore, this assignment can pass at least the third level of Bloom's Taxonomy and they feel that this is a good assignment and should be resumed for the next semester. This study recommends appointing the instructor to guide students in managing dialog efficiently.